Modal Features and Dynamic Behavior of a Nonlinear 3D Guyed Mast with Uncertain Guys Pretension - Ballaben, Jorge S. (2017)
The study of the nonlinear dynamic characteristics and response of a guyed mast, considering the uncertainty of the guys pretension is reported in this work. A computational model is constructed with the mast represented by an equivalent beam-column and the three guys at one level by cables with an initial pretension and only having tensile capacity. Starting from the energy formulation of beams and nonlinear cables, the continuous equations are discretized using finite element techniques, considering Hermite elements for the mast (Bernoulli beam theory) and quadratic elements for the nonlinear guys. Also, the second order effect due to the axial loads on the mast is taken into account. An ad hoc software, developed by the first author, is employed here to explore natural frequencies and modes of the structure considering the uncertainty propagation of the stochastic guys pretension. Since the guys design value can be modified at the construction stage and more, during the service life, the pretension force is modeled as a random variable with a probability density function (PDF) derived from the Principle of Maximum Entropy (PME). The model herein presented contributes to attain a more realistic description of the structure, mainly regarding the three-dimensional representation and the sensibility to the variability of the guys pretensions. The results here presented (natural frequencies and modes) obtained through an uncertainty quantification analysis, improve the understanding of the real dynamic properties and behavior of slender and flexible guyed structures.